Oral health status in Cienfuegos population - Emma Gil Ojeda; Beatriz García Alpízar; Yumaidy Colina Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: The creation of reliable epidemiological profiles in different populations is a helpful practice that offers a general vision of how community health can be affected and it assess health systems interventions and provides information to guide the policy making process. Objective: To assess the population´s oral health condition of through the determining of the appropriate markers. Methods: Descriptive study in five health areas of Cienfuegos province including people selected by age group and through randomized sampling. The oral health condition of this population was analyzed, and the results were compared with the previous measurement dating from 1998. Results: The percentage of this population between 5-18 years of age without malocclusions or gingival and periodontal affectation was 72,6% and 38,6% respectively; the percentage of children with DMF-index at the age of five was 1,96, while the 88,2% of 18 years-old surveyed people have all their teeth. The mean of lost teeth in the age groups 35-44 and 60-74 was 7,6 and 24,7 respectively. Conclusions: Most of oral health markers improved compared with the previous measurements, except for the age group 5-18 without malocclusions and the percentage of people without gingival or periodontal affectations, which was slightly reduced.